COMPLEX REHABILITATION OF CHILDREN WITH LIMITED LIFE ABILITIES - S.V. Osmolovskiy; V.N. Luchaninova; T.I. Burmistrova; D.S. Osmolovskiy (Вопросы современной педиатрии, 2011)
(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 175–177)